Peranan Gereja Terhadap Keluarga Yang Memilih Bercerai Dari Perspektif Konseling Pastoral - Parapat, Riyan Salomo (JURNAL DIAKONIA, 2021)
The church, which is a place of reconciliation for social life, should be able to pay attention to its people, in addition to serving the people with liturgical services, the word of God, and the sacraments, the church should also pay attention to pastoral care. In pastoral care, the Church provides assistance, which is referred to as "pastoral counseling" services, therefore the Church is expected to be able to answer the challenges of life faced by its people in daily life, as well as in family life. Problems will always exist, and may lead to divorce. Divorce that occurs in the midst of the people except for adultery is the negligence of the Church which pays little attention to its people. In completing this paper, the author uses qualitative research methods and literature studies, where the conclusion is Pastoral Counseling is a bridge in solving problems that exist in the midst of the family supported by prayer and hope for the common good.